A nationwide cohort study on the impact of gestational diabetes on future cardiovascular events. (3rd October 2022) - Bullough, S; Lip, G Y H; Fauchier, G; Herbert, J; Sharp, A; Bisson, A; Ducluzeau, P H; Fauchier, L
Abstract: Background: The link between hypertensive disease in pregnancy and future cardiovascular events is well established, as is the increased risk of developing type 2 diabetes mellitus after gestational diabetes (GDM). What is less well understood is the impact of GDM on future cardiovascular events. The literature is conflicting although suggestive that the risk of cardiovascular events with a history of GDM is 2 fold higher. Purpose: Using the largest cohort to date and utilising robust data acquisition procedures and follow up we assessed the prognostic value of GDM for future cardiovascular events. Methods: All female patients discharged from French hospitals in 2013 with at least 5 years of subsequent follow-up were identified. Those with a previous major adverse cardiovascular event, history of hypertensive disease, pre-existing diabetes or under the age of 18 years old were excluded. They were grouped depending on their history of GDM. After propensity score matching, patients with GDM were matched 1:1 with patients with no GDM. Hazard ratios for cardiovascular events during follow-up were adjusted by age at baseline. Results: A total of, 1, 738, 101 women were included in the analysis, leaving 1, 141, 743 women (mean age 52.2, SD 19.7) once exclusion criteria were applied: 6998 (0.6%) had a history of GDM and the mean follow-up was 5.1 years (SD 1.3 years). Those with a history of GDM had a lower risk of new onset heart failure (HF) (hazard ratio [HR] 0.66, 95% confidence interval [CI]: 0.45–0.98) and all-cause death (HR 0.61, 95% CI 0.47–0.79). There was no significant difference in risk for myocardial infarction (HR 0.88, 95% CI 0.38–2.03), ischaemic stroke (HR 0.94, 95% CI 0.55–1.63), new onset atrial fibrillation (AF) (HR 0.61, 95% CI 0.33–1.11), cardiovascular death (HR 1.25, 95% CI 0.47–3.36) and major cardiovascular events (i.e. in-hospital cardiovascular death, myocardial infarction, ischaemic stroke or new-onset HF (MACE-HF)) (HR 0.75, 95% CI 0.56–1.01). Conclusions: In a large contemporary analysis of female patient seen in French hospitals and utilising a robust data set we present the largest population analysis of the association between GDM and future cardiovascular events. Those with a history of GDM do not have a higher risk of myocardial infarction, ischaemic stroke, new onset AF, cardiovascular death or MACE-HF. Contrary to what is widely thought, a history of GDM confers a lower risk of new onset HF and all-cause death when compared to those women with no history of GDM. Funding Acknowledgement: Type of funding sources: None.